The Managerial Communication Skills of Heads of Departments in Secondary Schools in Seremban - P. M. Easaw, Elizabeth (1998)
This study is undertaken to ascertain the perception skill of Heads of Departments, to find out the strategies used by Heads of Departments to lubricate the communication flow in schools and to determine whether Heads of Departments possess team building characteristics. Two sets of questionnaires were distributed to thirty three Heads of Departments and ninety six teachers from nine Grade A secondary schools in Seremban, Negeri Sembilan. One set of questionnaire was designed to determine the perception skill and the managerial communication skills and the team building characteristic of the Heads of Departments. The respondents to this questionnaires were Heads of Departments. Another set of questionnaire was designed to determine the motivating language scale of Heads of Departments. The respondents to this questionnaire were the teachers from the various Departments.The findings indicated that majority of the Heads of Departments have low perception skills, high managerial communication skills and a high level of characteristics of team building spirit. The Heads of Departments also use a high level of motivating language in direction giving, empathetic language, mean making language and in communication satisfaction when communicating with the teachers in their Departments.